2020
DOI: 10.3390/pathogens9070554
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Immunological Features of Human Leishmania (L.) infantum-Infection, Novel Insights Honduras, Central America

Abstract: Leishmania (Leishmania) infantum is the etiological agent of both American visceral leishmaniasis (AVL) and non-ulcerated cutaneous leishmaniasis (NUCL) in Honduras. Although AVL is the most severe clinical form of infection, recent studies have shown that human immune response to parasite infection can result in a clinical-immunological spectrum. The overall prevalence rate of infection and clinical-immunological profiles of the L. (L.) infantum infection in Amapala municipality, South Honduras was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 45 publications
1
16
0
7
Order By: Relevance
“…In addition, we showed that patients with NUCL produce very little antibody, since only 19% of them were seropositive and always had low titers of specific IgG or IgM antibodies. On the other hand, 56% of these patients showed a strongly positive intradermal Montenegro reaction [23], reinforcing the findings of an effective cellular immune response of the host against L. (L.) infantum chagasi.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In addition, we showed that patients with NUCL produce very little antibody, since only 19% of them were seropositive and always had low titers of specific IgG or IgM antibodies. On the other hand, 56% of these patients showed a strongly positive intradermal Montenegro reaction [23], reinforcing the findings of an effective cellular immune response of the host against L. (L.) infantum chagasi.…”
Section: Discussionsupporting
confidence: 77%
“…In some countries of South America, these lesions clinically can be papular, nodular, or ulcerated with or without the presence of crust [ 8 - 11 ]. However, in Central America [ 4 , 12 - 14 , 23 ], the patients presented small nodular lesions that do not cause ulcer independent of the evolution time of infection.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with clinical signs of VL or NUCL were submitted to clinical and laboratory examinations. VL diagnosis was confirmed by rK39 dipstick test (InBios International); and NUCL diagnosis was confirmed by the presence of Leishmania amastigotes in smear of cutaneous lesion stained by Giemsa, as already reported 11 . Parasites were isolated from VL and NUCL patients and L .…”
Section: Methodsmentioning
confidence: 85%
“…( L .) infantum chagasi , a predominantly cellular immune response characterized by positive DTH has been shown in NUCL associated to weak humoral immune response 11 . It is important to mention that in human cutaneous leishmaniasis caused by different species of dermatropic parasites, low‐to‐moderate levels of specific anti‐ Leishmania IgG antibodies have been reported in the serum of patients; and its role on the evolution of infection remains unclear 33,34 …”
Section: Resultsmentioning
confidence: 99%
“…The two Leishmania species isolates used in this work were (i) L. infantum chagasi MHOM/HD/2017/M32502/Amapala District/Honduras, which was isolated from a human case of nonulcerated cutaneous leishmaniasis according to procedures approved by the Research Ethics Committee of the Medical School of São Paulo University (CAAE protocol number 64223917.1.0000.006) ( 8 ), and (ii) L. infantum chagasi MCER/BR/1981/M6445/Salvaterra/Pará State/Brazil, which was isolated from a crab-eating fox ( Cerdocyon thous ), the wild reservoir ( 6 ). Both L. infantum chagasi isolates were grown at 25°C for 7 days in Schneider medium supplemented with 10% fetal bovine serum, 10 μg/ml 1% l -glutamine, and 100 IU/mL ampicillin.…”
Section: Announcementmentioning
confidence: 99%